2012
DOI: 10.1007/s11434-012-5407-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in alpine grassland phenology in the Qinghai-Tibetan Plateau from 1999 to 2009

Abstract: Plant phenology is the most salient and sensitive indicator of terrestrial ecosystem response to climate change. Studying its change is significantly important in understanding and predicting impressively changes in terrestrial ecosystem. Based on NDVI from SPOT VGT, this paper analyzed the spatiotemporal changes in alpine grassland phenology in Qinghai-Tibetan Plateau from 1999 to 2009. The results are enumerated as follows: (1) The spatial distribution of the average alpine grassland phenology from 1999 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 35 publications
(51 reference statements)
8
87
1
2
Order By: Relevance
“…The HANTS method was employed in the present work to carry out a smoothing treatment of the NDVI data obtained from GIMMS and SPOT-VGT. As a result of the HANTS treatment, two types of data were obtained: one comprised smoothed data having the same temporal resolution as the raw data; the other was the smoothed data with a temporal resolution of 1 day (Ding et al, 2013). Smoothed data were used only in Methods 1, 2 and 3 but not in Method 4.…”
Section: Preprocessing Of Ndvi Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The HANTS method was employed in the present work to carry out a smoothing treatment of the NDVI data obtained from GIMMS and SPOT-VGT. As a result of the HANTS treatment, two types of data were obtained: one comprised smoothed data having the same temporal resolution as the raw data; the other was the smoothed data with a temporal resolution of 1 day (Ding et al, 2013). Smoothed data were used only in Methods 1, 2 and 3 but not in Method 4.…”
Section: Preprocessing Of Ndvi Datamentioning
confidence: 99%
“…One study based on MODIS NDVI data showed that the alpine vegetation SGS advanced in most parts of the TP between 2001 and 2010 (Song et al, 2011). Two of the other studies based on SPOT-VGT NDVI data found an SGS delay between 1998and then an advancement between 2003(Shen, 2011Ding et al, 2013). Zhang et al (2013) have found that the GIMMS NDVI data for 2001-2006 differs substantially from the corresponding SPOT-VGT NDVI data and MODIS NDVI data and they have suggested that the GIMMS NDVI data may suffer from severe data-quality issues in most parts of the western plateau, so they thought that the SGS advanced continuously after the end of the 1990s based on SPOT-VGT NDVI data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation coverage serves asgrowth of plants (Gurgel and Ferreira 2003). Furthermore, climate change has become a critical point in global change research (Ding et al 2013). Dramatic climate change has been confirmed over the past several decades in several studies (Namgail et al 2012) with an observed increase of 0.6±0.2°C in global mean surface temperature (Zhao et al 2004), leading to more rapid melting of ice, especially in regions of high altitude.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the monthly correlation coefficient for monthly average Normalized Difference Vegetation Index (NDVI) and precipitation is 0.75, which is greater than the correlation coefficient of 0.63 for monthly average NDVI and temperature in the Lhasa area (Chu et al 2007). Previous studies have analyzed NDVI variations and their relationships with temperature and precipitation in the Tibetan Plateau (Chu et al 2007;Xu et al 2011;Ding et al 2013;Wang et al 2015), but correlations between NDVI in different vegetation types and climatic factors have not been observed. In actuality, different vegetation types respond differently to temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%